Variaisi Bahasa dalam Slogan Iklan Produk Kecantikan di Tiktok Tahun 2025-2026 - Nuril Isabillah; Magfirotul Hamdiah (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aims to describe language variation and language functions in beauty product advertising slogans on TikTok during 2025–2026. A descriptive qualitative method with a sociolinguistic approach was employed. The data consist of words, phrases, and sentences found in beauty product advertising slogans posted on TikTok accounts of skincare brands, cosmetics brands, and beauty influencers. Data were collected through observation and note-taking techniques, while data analysis followed the stages of data reduction, classification, interpretation, and drawing conclusions. The findings reveal that TikTok beauty advertising slogans are predominantly characterized by code-mixing (Indoglish) and slang varieties. These language forms are used to create a modern, trendy, and engaging impression that aligns with digital communication culture. In addition, the dominant language functions identified are informative and persuasive (conative) functions. The informative function is used to deliver product information, while the persuasive function aims to influence consumers’ purchasing decisions. Overall, the use of language variation in TikTok beauty advertising slogans indicates that language in digital media functions not only as a means of communication but also as a marketing strategy and a representation of contemporary lifestyle, particularly among Generation Z users.